ANÁLISE DA OCORRÊNCIA DE BOLORES EM EDIFICAÇÕES COM PAREDES DE CONCRETO - Afonso, Thiago Martin; Brito, Adriana Camargo de; Akutsu, Maria (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
In the recent Brazilian construction scenario, the use of a construction system with solid concrete walls has been growing, especially in social housing programs. But some problems have been detected in this kind of buildings, particularly the mould fungus formation on the interior surface of the envelope walls. This paper purpose is to analyze this problem, studying a real housing development with mould problems, under the light of a proposed model in the literature, for prediction of mould growth in interior surfaces. Secondarily, this paper aims to determine possible parameters that determine the occurrence of the mould in the studied dwellings.